Counselor Personality and The Development of Personal Theory in Behavioristic Counseling: A Literature-Based Exploration - Nuha, Moch. Syihabudin; Lismaini, Lismaini; Hidayah, Nur; Wahyuni, Fitri (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
The professionalism of the counselor is judged by how well he understands himself first before seeing the problem or potential or understanding the counselee. The counselor over time in applying his knowledge can integrate the theory of techniques that are best understood and mastered, so that the counselor has his own style. Counselors in choosing their personal counseling theory use a counseling theory approach assessment instrument developed by Finch. The research method used is literature study and phenomenology which is carried out by finding literature sources, reading literature, selecting literature and analyzing related literature. Counselor professional development can be done through the development of counseling personal theory identity. This development will be very useful for counselors in showing characteristics, consistency, attractiveness and efficiency in the counseling process. The discovery of specialization in the field of counseling is carried out with 6 steps, namely understanding values and self-beliefs, deepening counseling theories and techniques, examining each theory and technique, practicing theories and techniques, integration and personalization. Counselor specialization in the field of behavioristic counseling is closely related to how the counselor's personal philosophy adheres to that everything that happens to the counselee is a consequence of the surrounding environment or antecedents. The discovery of a personal theory of counseling will be very useful for a counselor in his confidence in counseling practice, so that he is able and competent in applying the theory that has found its distinctiveness.